Patients and clinicians managing patellofemoral pain should not rely on general web-based information - de Oliveira Silva, Danilo [UNESP]; Rathleff, Michael Skovdal; Holden, Sinead; Bell, Emily [UNESP]; Azevedo, Fábio [UNESP]; Pazzinatto, Marcella Ferraz [UNESP]; Barton, Christian (Elsevier, 2020)
Objective: To evaluate the credibility and accuracy of PFP-specific web-based content. Design: Cross-sectional evaluation of web-based information. Methods: The study protocol was registered with PROSPERO (CRD42018088671). Two search engines (Google and Bing) were used to search for websites offering information about PFP. Two reviewers assessed the websites for credibility-related and PFP-specific content. PFP-specific content was evaluated according to agreement with current international PFP consensus statements. Based on this, content was rated as (i) Accurate/Clearly described; (ii) Partially accurate/Description lacks clarity; (iii) Inaccurate/Misleading description; or (iv) Not mentioned. Results: After exclusion of duplicates, forty online websites were included in our analyses. 43% of websites did not mention their source of information, and 48% did not mention if the source material was peer-reviewed. Misleading/inaccurate information was most commonly found in the definition of PFP (20% websites) and clinical examination (15%). Twenty-two percent of websites recommended surgery as treatment. The item most frequently rated as accurate/clearly described was PFP terminology (87.5%). Conclusion: This study highlights missing, inaccurate or poorly described web-based PFP information. Due to the commonality of PFP and potential for improving self-management, there is an urgent need to develop more accurate and comprehensive web-based patient education resources for PFP.
Keywords: Anterior knee pain; Consumer health information; Education; Internet; Knee